Whole Body Treatment: Introduktion - Schultz, Laura Luise (Peripeti, 2021)
A performance essay with stage directions. An artistic reflection on working with the performance series Whole Body Treatment version 1 - 4. The performance explores new formats like theater on the body, the series, the 1:1 performance. The performance essay reflects on the different experiences with these new formats.